Bile acids, gut microbiota and metabolic surgery - Tu, Jui; Wang, Yangmeng; Jin, Lihua; Huang, Wendong (Frontiers in Endocrinology, 2022)
Metabolic surgery, or bariatric surgery, is currently the most effective approach for treating obesity and its complications. Vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) are the top two types of commonly performed metabolic surgery now. The precise mechanisms of how the surgeries work are still unclear, therefore much research has been conducted in this area. Gut hormones such as GLP-1 and PYY have been studied extensively in the context of metabolic surgery because they both participate in satiety and glucose homeostasis. Bile acids, whose functions cover intestinal lipid absorption and various aspects of metabolic regulation via the action of FXR, TGR5, and other bile acid receptors, have also been actively investigated as potential mediators of metabolic surgery. Additionally, gut microbiota and their metabolites have also been studied because they can affect metabolic health. The current review summarizes and compares the recent scientific progress made on identifying the mechanisms of RYGB and VSG. One of the long-term goals of metabolic/bariatric surgery research is to develop new pharmacotherapeutic options for the treatment of obesity and diabetes. Because obesity is a growing health concern worldwide, there is a dire need in developing novel non-invasive treatment options.